Parallaxes : Virginia Woolf meets James Joyce - Canani, Marco; Sullam, Sara, 1979- (Cambridge Scholars Publishing, 2014)
Borrowed from optics, the concept of parallax identifies the apparently relative position of objects according to the lines of sight determined by the viewer's standpoint. This concept proves particularly useful in opening new insights into the work of two major authors of Modernist literature: although coincidentally born and deceased in the same years (1882-1941), James Joyce and Virginia Woolf are seldom the object of a joint outlook. Such a watertight separation is witnessed by the scarcity of scholarly work concerned with the relationship between two authors who, on the other hand, often feature together in studies and anthologies on Modernism. Parallaxes fills this void by tackling the many implications of Woolf and Joyce's difficult--if not failed--encounter, and provides new perspectives on the connections between their respective work. The essays in this volume investigate the works of the two writers--seven decades after their death--from a variety of angles, both singularly and jointly, stimulating dialogue between scholars in both Woolf and Joyce studies